Features of legal regulation transplantations in Ukraine - Iasechko, S. V.; Ясечко, С. В.; Stepanenko, T. V.; Степаненко, Т. В.; Korolova, V.; Makovetska, N.; Chernetchenko, O.; Svitlana Iasechko (Journal of Critical Reviews. – 2020. – № 7 (13). – Р. 430-432, 2020)
Наукова робота присвячена актуальній проблемі розвитку вітчизняної медицини, а саме служби трансплантології України. Проведено аналіз сучасних проблем трансплантаційної галузі. Авторським колективом виявлено, що основною проблемою є відсутність єдиної правової системи трансплантології. У статті аналізується стан законодавчого регулювання трансплантології та механізми її реалізації. У статті розглядаються основні аспекти розвитку договірних відносин у сфері трансплантації органів та правові акти, що регулюють донорство органів.

The scientific work is devoted to the urgent problem of native medicine development, and exactly to the transplantation service of Ukraine. The analysis of modern problems of transplantation industry was carried out by the authors’ team in their work, the main problem is the absence of the unified organ law system. This article analyzes the state of legislative regulation of transplantation and mechanisms for their implementation. The article considers the main aspects of the development of contractual relations in the field of organ transplantation and legal acts that regulate the donation of organs and other human anatomical parts, which have expired and those which are valid today.

Научная работа посвящена актуальной проблеме развития отечественной медицины, а именно службы трансплантологии Украины. Проведен анализ современных проблем трансплантационной отрасли. Авторским коллективом выявлено, что основной проблемой является отсутствие единой правовой системы трансплантологии. В статье анализируется состояние законодательного регулирования трансплантологии и механизмы его реализации. В статье рассматриваются основные аспекты развития договорных отношений в сфере трансплантации органов и правовые акты, регулирующие донорство органов.
Keywords: Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Цивільне право. Civil Law. Гражданское право; трансплантологія; статус; донор; отримувач; зобов'язання; медичні послуги; transplantology; status; donor; recipient; obligation; medical services; трансплантология; статус; донор; получатель; обязательство; медицинские услуги